SUMBER DAYA MANUSIA TRANSPORTASI, TELEKOMUNIKASI, DAN PARIWISATA DALAM PERSPEKTIF GLOBAL - Budi Purwanto; Salahudin Rafi; Hentje Pongoh (Institut Transportasi dan Logistik Trisakti, 2016)
The purpose of this study is to assess the human resources sectors of transport, telecommunications and tourism in a global perspective. This study is a literature study with descriptive analysis method to describe the existing problems and provide recommendations to anticipate the world’s rapidly growing trend. The results show that the increasing mastery of foreign languages and technology has become an absolute requirement that Indonesian human resources can compete on a global level. However, the state, business, and society must work together in forming a mental attitude, promote an understanding of the religion, and raise the nation ideology since early stage so that it can minimize the negative impacts of globalization.